The carotid body detects circulating tumor necrosis factor-alpha to activate a sympathetic anti-inflammatory reflex - Katayama, Pedro L. [UNESP]; Leirão, Isabela P. [UNESP]; Kanashiro, Alexandre; Luiz, João P.M.; Cunha, Fernando Q.; Navegantes, Luiz C.C.; Menani, Jose V. [UNESP]; Zoccal, Daniel B. [UNESP]; Colombari, Débora S.A. [UNESP]; Colombari, Eduardo [UNESP] (Elsevier, 2022)
Recent evidence has suggested that the carotid bodies might act as immunological sensors, detecting pro-inflammatory mediators and signalling to the central nervous system, which, in turn, orchestrates autonomic responses. Here, we confirmed that the TNF-α receptor type I is expressed in the carotid bodies of rats. The systemic administration of TNF-α increased carotid body afferent discharge and activated glutamatergic neurons in the nucleus tractus solitarius (NTS) that project to the rostral ventrolateral medulla (RVLM), where many pre-sympathetic neurons reside. The activation of these neurons was accompanied by an increase in splanchnic sympathetic nerve activity. Carotid body ablation blunted the TNF-α-induced activation of RVLM-projecting NTS neurons and the increase in splanchnic sympathetic nerve activity. Finally, plasma and spleen levels of cytokines after TNF-α administration were higher in rats subjected to either carotid body ablation or splanchnic sympathetic denervation. Collectively, our findings indicate that the carotid body detects circulating TNF-α to activate a counteracting sympathetic anti-inflammatory mechanism.
Keywords: Carotid body; Inflammation; Neural circuits; Neuroimmune interactions; Neuroimmunomodulation; Sympathetic nervous system